Exosome engineering for targeted therapy of brain-infecting pathogens: molecular tools, delivery platforms, and translational advances - Onohuean, Hope; Naik Bukke, Sarad Pawar; Thalluri, Chandrashekar; Abass, Kasim Sakran; Choonara, Yahya Essop (Frontiers in Medical Technology, 2025)
Central nervous system (CNS) infections caused by pathogens such as HIV, Herpes simplex virus, Cryptococcus neoformans, and Toxoplasma gondii remain among the most difficult to treat due to the physiological barrier posed by the blood-brain barrier (BBB), pathogen latency, and systemic toxicity associated with conventional therapies. Exosome-based delivery systems are becoming a game-changing platform that can solve these therapeutic problems using their natural biocompatibility, minimal immunogenicity, and capacity to cross the BBB. This review current developments in exosome engineering that aim to make brain-targeted therapy for neuroinfectious illnesses more selective and effective. Much focus is on new molecular methods like pathogen-specific ligand display, aptamer conjugation, lipid modification, and click–chemistry–based surface functionalisation. These methods make it possible to target diseased areas of the brain precisely. Exosomes can also carry therapeutic payloads, such as anti-viral and antifungal drugs, gene editing tools like CRISPR/Cas9 and siRNA, and more. This makes them helpful in changing pathogens' persistence and the host's immunological responses. The paper tackle problems with translation, such as biodistribution, immunogenicity, GMP production, and regulatory issues. Future possibilities like synthetic exosomes, combinatory medicines, and delivery design that uses AI. The combination of nanotechnology, molecular biology, and infectious disease therapies shows that exosome engineering offers a new way to meet the clinical needs that are not satisfied in treating CNS infections.